Design and Analysis of a Small Formula-Style Race Car Suspension System - Wan Amirudin bin Wan Mohamad Noor, Wan Amirudin (Universiti Teknologi Petronas, 2009)
This report is prepared to describe the project of designing a suspension system for a small race car. The objective of the project is to design a new suspension system that would work in the new chassis design. The project is initiated as the previous suspension system could not fit into the new chassis design. Among the methodology used is the simulation of the suspension system using MSC. Adams Car. The simulation is done to test the performance of the designed suspensions. Next, CATIA is used to model the components of the suspension that will be used in the race car. In the end of the report, the suspension system to be used in the new chassis design has been identified. From the methodology, the suspension system that will be used in the new chassis is the double wishbone suspension with pushrod actuation. The suspension geometries are negative 2˚ camber angle, positive 3˚ caster angle and positive 1˚ toe angle.